Human Conception in Education in the Context of Mulla Sadra's Theory of Substantial Motion (al-Haraka al-Jawhariyya) - Dali, Ana Bilim (Şırnak Univ, 2023)
The discussions regarding motion, may be one of the most ancient topic in the philosophical tradition, not only shed light on the entire existence but also offer insights into the conception of human beings. Each inquiry into the nature of motion leads to broader answers, unveiling the essence of human beings who actualize their existence through continuous movement. Traditionally, motion theories built on the notions of the immutability of substance or the motion of accident have considered humans as entities in motion, yet fundamentally unchanged, with an external mover. In contrast, Mulla Sadra's theory of substantial motion (al-Haraka al-Jawhariya) proposes that motion inherently occurs within the essence of existence, suggesting that humans are in a perpetual state of change and transformation at their core, serving both as the agent (muharrik) and the object (mutaharrik) of this change. Although many Islamic philosophers propose that motion is only limited to four categories, including quantity (kamiyyah), quality (kayfiyyah), place, and position, Mulla Sadra challenges this notion by arguing that motion and change can directly occur within the category of substance itself. Consequently, Sadra's theory of trans-substantial motion presents the possibility to contribute to the understanding of education and the perception of human beings. Therefore, the text at hand is not a verification or validation study, but rather a product of examination and interpretation. From this limited standpoint, the educational implications and potential outcomes that can be subjected to analysis are as follows: In Mulla Sadra's thought, the moving substance is an ontological reality that moves itself. The human soul (nafs), being a substance as well, is in constant motion, with the agent of its motion residing within itself. From an educational perspective, this approach highlights the potential for profound metamorphic transformations in humans and promotes a dynamic and proactive understanding of human beings. Thus, education can unveil at least two of its causality principles: the agent (subject) and the object (object). In the context of substantial motion, where the mover and the moved are identical, external factors play a minimal role, merely serving as preparatory and supportive elements. In other words, in education, the individual is both the one being formed and the one being the agent of formation. External factors, such as instruction and the instructor, are not the true formers. Therefore, education entails a process of self-becoming, coming into existence, and accumulation, which involves the simultaneous presence of power and action. Departing from contemporary dominant educational approaches that prioritize teaching and pedagogy, this perception of human beings encourages a focus on the essence of individuals, which is likely to prompt our discipline to engage in significant insights.
Keywords: Religious Education; Philosophy of Education; Human; Mulla Sadra; Substance; Motion; Substantial Motion